Thickness influence in mechanical properties of polyurethane adhesive overlap joints - García-Ledesma, R.; Oñoro, J.; Amo, J. M.; Durán, M. C.; Durán, J. (Revista de Metalurgia, 2005)
The thickness of adhesive layers in metallic bonded joints has direct influence in the performance and mechanical behaviour of these joints. The aim of this study was to analyse the strength and strain properties of steel overlap joints bonded with polyurethane adhesive layers with different thickness. The results show that the strength is maximum when the thickness of the adhesive layer is very thin, 0.1 mm. When the thickness growth to 1 mm the strength goes down rapidly. For layers from 1 to 1.5 mm the strength goes down slower and from 1.5 to 4 mm the strength is nearly constant. In other hand, the joint strain increase uniformly with adhesive layer thickness growth.